Comentario al caso Usón Ramírez vs. Venezuela. Sentencia de la Corte Interamericana de 20 de noviembre de 2009 - Mosquera Monelos, Susana (Revista de Derecho, 2020)
Usón Ramírez case is the fifth case against Venezuela exanimate by the Interameri-can Court of Human Rights during 2009. It is a leading case because of the public relevance of Mr. Usón, a former official of the Venezuelan army forces, which even was a member of the Chavez government. Mr. Usón, is an official on retirement situation judged by a military court, violating his fundamental rights to a competent and impartial judge, because of a rigorist use of military justice. The Uson Ramírez case shows the good health of the Interamerican system of human rights protection.
Keywords: freedom of speech; injury; personal freedom; proportionality test; military justice; democracy; rule of law